The Influence of Leader Emotional Intelligence, Transactional Leadership and Perceived Organizational Support on Job Performance Mediated by Trust in Supervisor - Yusnita, Iing (Transpublika Publisher, 2025)
The primary objective of this research is to explore how the emotional intelligence of a leader, transactional leadership, and perceived organizational support impact job performance through the lens of trust in a supervisor. To collect quantitative data, a non-probability sampling technique was utilised, and an online questionnaire was distributed to 105 employees in Plaza Harco Mangga Dua, Jakarta, who hold supervisory positions and have been with the company for more than a year. Analysis of the data was conducted using SmartPLS-4 software. The findings revealed that leader emotional intelligence, transactional leadership, and perceived organizational support all have a beneficial influence on job performance. Additionally, leader emotional intelligence and transactional leadership were found to positively impact trust in supervisors, and perceived organizational support was also linked to higher levels of trust in supervisors, which in turn influenced job performance positively. In the analysis of mediation, it was found that trust in the supervisor plays a significant role in linking leader emotional intelligence, transactional leadership, and perceived organizational support to job performance. This study indicates that the aforementioned factors have a strong impact on job performance and can accurately predict it (R2 = 0.553, Q2 = 0.356). Moreover, this model also shows a high level of predictability when it comes to trust in the supervisor (R2 = 0.636, Q2 = 0.429). Based on research findings, Plaza Harco Mangga Dua Jakarta management should enhance leader emotional intelligence, transactional leadership, and perceived organizational support to improve employee performance and build trust in leadership.